Q. 3 F5.0( 2 Votes )

# Prove the following identities.(1 + cotθ – cosec θ)(1 + tanθ + secθ) = 2

Consider LHS,

LHS = (1 + cotθ – cosecθ) (1 + tanθ + secθ)

Expanding the above,

(1 + cotθ – cosecθ) (1 + tanθ + secθ)

= 1 + tanθ + secθ + cotθ + cotθtanθ + cotθsecθ – cosecθ –cosecθtanθ –cosecθsecθ

We know that = secθ, = cosecθ, = tanθ and = cotθ.

= 1 + tanθ + secθ + cotθ + 1 + cosecθ – cosecθ – secθ – cosecθsecθ

We know that tanθ + cotθ = cosecθsecθ.

= 1 + cosecθsecθ – cosecθsecθ + 1

(1 + cotθ – cosecθ) (1 + tanθ + secθ) = 2 = RHS

Hence proved.

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Related Videos
Champ Quiz | Trigger on Trigonometry47 mins
Basics of TrigonometryFREE Class
NCERT | Trigonometric Identities52 mins
Champ Quiz | Trigonometry Important Questions33 mins
Solving NCERT Questions on Trigonometric Identities56 mins
NCERT | Imp. Qs. on Trigonometry42 mins
Quiz | Trail of Mixed Questions on Trigonometry59 mins
Champ Quiz | NTSE Trigonometry50 mins
Testing the T- Ratios of Specified Angles57 mins
Foundation | Cracking Previous Year IMO QuestionsFREE Class
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
view all courses